Análise do comportamento vibratório da membrana de um shaker eletrodinâmico - Ferreira, Thiago Menegheti (2017)
A constant challenge in the field of technology is to look for the evolution of computing resources or of machinery that contribute to the development and the work done by man. Among the branches in which computers are widely used, engineering is a field that certainly relies on this technology to improve its projects. With this in mind, this work aims to describe concepts that help to understand the operation of an electrodynamic shaker, a vibrating excitation device fed by a sinusoidal harmonic force. The work has a great theoretical basis for the execution of calculations that will be modeled mathematically and simulated computationally. Subjects such as vibration, electromagnetism and electrical are the focus of the calculations. Throughout this text, application examples of a shaker will be showed bringing the reader closer to the topic addressed. The results obtained are discussed and expressed in tables and graphs for a good understanding of the acquired values. A brief step by step modeling of the computational prototype is also described in this work as well as the guidelines of the computational simulations carried out in software, available in the body of this work in the form of figures. Comparisons between the expected behavior of the vibratory system and the one obtained in this work are arranged in order to express a relation between the input and output parameters of the system, finishing the work done.